Analysis Of The Work Motivation Factors On An Employee Performance - Laila Irawati; Khaeruman; Yuary Farradia (CV. Inara, 2021)
The importance of motivation is because motivation is the cause and supporter of human behavior so that they are willing to work hard and enthusiastically to achieve optimal results. Motivation is increasingly important in an organization or company because the leader distributes work to his staff to be done well and integrated to achieve the desired goals.The method used in this study refers to the